2013
DOI: 10.1111/clr.12149
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of buccal soft tissue recessions around single implants: 1‐year results from a prospective pilot study

Abstract: Aim: The aim of this study was to evaluate the outcome of a soft tissue dehiscence coverage technique, at single non-submerged implant sites, presenting shallow isolated buccal mucosal recession. Material and methods:Sixteen patients were included in this prospective study. A connective tissue graft (CTG) was harvested from the maxillary tuberosity. The donor soft tissue was de-epithelialized and trimmed with a mucotome for an optimal adaptation to the collar of the implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
127
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(165 citation statements)
references
References 24 publications
0
127
1
Order By: Relevance
“…2 The peri-implant mucosa should be augmented to prevent or treat mucosal recession. [3][4][5] The enhancement of soft-tissue thickness (STTh) around dental implants may also be required to avoid shimmering through implant parts, especially those made of titanium. 6 Particularly, in the esthetic zone, CTGs have become the first-line therapy.…”
Section: Introductionmentioning
confidence: 99%
“…2 The peri-implant mucosa should be augmented to prevent or treat mucosal recession. [3][4][5] The enhancement of soft-tissue thickness (STTh) around dental implants may also be required to avoid shimmering through implant parts, especially those made of titanium. 6 Particularly, in the esthetic zone, CTGs have become the first-line therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although a FGG from the maxillary tuberosity (tFGG) can only be harvested by performing a gingivectomy, a CTG from the tuberosity (tCTG) can be obtained with a distal wedge procedure or by removing a gingival cuff and performing the de‐epithelialization extraorally …”
Section: Harvesting Approaches From Maxillary Tuberositymentioning
confidence: 99%
“…Soft tissue grafts from the tuberosity are increasingly gaining popularity because of their ease in harvesting, the presence of low fatty or glandular tissue, and the richness in connective tissue fibers . Additionally, harvesting from the tuberosity presents minimal risk of intraoperative or postoperative complications, resulting in reduced patient morbidity .…”
Section: Introductionmentioning
confidence: 99%
“…The results after a one‐year follow‐up showed 96.3% average coverage with a complete coverage of 75% of peri‐implant sites treated. On the other hand, some authors have considered the possibility of maintaining the existing crown . Burkhardt et al showed only 66% coverage when keeping the crown.…”
Section: Proposed Therapeutic Approachesmentioning
confidence: 99%
“…Burkhardt et al showed only 66% coverage when keeping the crown. However, Rocuzzo et al also proposed removing the crown before surgery and achieved an average coverage of 89.3%, with complete coverage of nine out of 16 peri‐implant treated sites. In the experience of the authors, attempting reconstruction while maintaining the permanent prosthesis complicates the accommodation of the graft and flap repositioning.…”
Section: Proposed Therapeutic Approachesmentioning
confidence: 99%